Prevalence of oncopatology risk factors among residents of the Omsk region - O. N. Kruch; D. V. Turchaninov; E. A. Vilms; N. G. Shirlina (Фундаментальная и клиническая медицина)
Aim. To assessment the prevalence of cancer risk factors in various population groups of the Omsk region.Materials and Methods. The descriptive, cross-sectional epidemiological study included residents of the Omsk region (n = 542) aged 18 to 83 years. To obtain the data, we performed a survey which included questionnaires on the daily patterns and frequency of food consumption, eating habits, and health status. In addition, we assessed the prevalence of smoking, alcohol consumption, physical activity, family history of cancer, overweight.Results. At least one of the studied risk factors was present in 80.1 ± 1.7% of the adult population, including 84.9% of men and 76.3% of women (p = 0.030). The most common factors were: excessive consumption (> 500 g/week) of red and processed meat (55.8 ± 2.1%), overweight (53.6 ± 2.1%), excessive consumption of dietary salt (44.2 ± 2.1%), frequent alcohol consumption (39.3 ± 2.1%), and low physical activity (29.8 ± 2.1%). The smoking was more prevalent in the male population (37.0 ± 3.13%). Although overall alcohol consumption was below the Russian average, excessive alcohol consumption was still found in 21.9% of men and 12.8% of women. The combination of smoking and excessive consumption of alcohol was also more frequent in male population (26.8 ± 2.1%). The proportion of people with consumption of fresh vegetables and fruits < 500 g/day (including potatoes) was 42.6 ± 2.12%. The content of dietary fiber in the diet in an amount < 20 g/day was noted in 57.8 ± 2.1% of the study participants. In men, the average daily salt intake was significantly higher compared to women (6.24 g and 5.20 g, respectively; p = 0.001).Conclusion. The prevalence of cancer risk factors among the residents of the Omsk region was assessed as high and generally does not tend to decrease.